Considerations on the Automation of Financial-Accounting Systems for Enhancing Decision-Making Processes at the Level of Economic Entities - Soare, Janina Georgiana; Panait (Ion), Mihaela; Munteanu, Victor (Acta Universitatis Danubius. Œconomica, 2025)
This research study aims to explore the role of information technology in the activities of economic entities by integrating automation into their financial-accounting information systems. In this regard, an analysis was conducted on various Enterprise Resource Planning (ERP) systems, whose information was available online, with the objective of defining a qualitative model for optimizing electronic processes from a financial-accounting perspective. The model was developed based on the analysis of processes specific to the efficient management of supplier liabilities. Initially, the study identified the activities and processes that contribute to the effective handling of liabilities towards suppliers. Subsequently, a comparative analysis was carried out between computerized and traditional accounting, highlighting the rudimentary nature of the latter. This deficiency stems from additional costs caused by human and material errors, as well as the excessive time required for economic activities, which in turn impacts overall results. The proposed solution for improving economic efficiency in its entirety involves the automatic generation of updated and real-time financial reports and statements. This approach provides a comprehensive view of the entity’s financial and economic status, thereby facilitating the decision-making process at the management level, with a direct and immediate impact on overall performance.